USING JEOPARDY GAME TO IMPROVE STUDENTS’ READING COMPREHENSION OF THE EIGHTH GRADE IN UPT SPF SMP NEGERI 35 MAKASSAR - Mursyidah Dianti Thohirah; Siti Haliah Batau; Ulfah Syam (Lembaga Jurnal FKIP Universitas Bosowa, 2023)
This research aimed to determine the use of Jeopardy Game learning media on Reading Comprehension Skills of Narrative Text by Eighth Grade students of UPT SPF SMP Negeri 35 Makassar. This research focused on quantitative experimental research. The population of this research was students of class VIII UPT SPF SMP Negeri 35 Makassar, totaling 282 students. Random Sampling technique was used to one class as research sample, which consisted of 28 students. The data were obtained from written tests related to reading comprehension on narrative text. The results of this study used inferential analysis of the t-test by SPSS v.16 which showed a significant effect on the students’ mean score of Reading Comprehension skill between the pretest and post-test. The mean score of the students’ Reading Comprehension on Nrrative Text enhanced from 3.39 in the pretest to 6.46 in the posttest. The significance value calculated 0.000 is smaller than 0.05 (P-value = 0.000 < 0.05). Thus, it can be concluded that Jeopardy Game learning media is effect applied to students’ Reading Comprehension skill on Narrative Text in class VIII at UPT SPF SMP Negeri 35 Makassar.